2011
DOI: 10.1128/aem.00090-11
|View full text |Cite
|
Sign up to set email alerts
|

Increased Transfer of a Multidrug Resistance Plasmid in Escherichia coli Biofilms at the Air-Liquid Interface

Abstract: Although biofilms represent a common bacterial lifestyle in clinically and environmentally important habitats, there is scant information on the extent of gene transfer in these spatially structured populations. The objective of this study was to gain insight into factors that affect transfer of the promiscuous multidrug resistance plasmid pB10 in Escherichia coli biofilms. Biofilms were grown in different experimental settings, and plasmid transfer was monitored using laser scanning confocal microscopy and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 70 publications
3
81
2
Order By: Relevance
“…Plasmids of incompatibility group F are among the most prevalent antibiotic resistance plasmids in Enterobacteriaceae species [10]. Plasmids of the incompatibility group FII were identified as the main vehicles of bla CTX-M-15 in E. coli and K. pneumoniae, as well as for other antibiotic genes conferring resistance to tetracyclines, aminoglycosides and fluoroquinolones present on IncFII plasmids along with ESBL genes [4,11,22]. Most of the K. pneumoniae isolates as well as other Enterobacteriaceae isolates, including multiresistant epidemiological clone E. coli B2-O25b-ST131, in this study harboured large IncFII K plasmids with multiple antibiotic resistance genes and showed conjugative ability to E. coli as well as Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids of incompatibility group F are among the most prevalent antibiotic resistance plasmids in Enterobacteriaceae species [10]. Plasmids of the incompatibility group FII were identified as the main vehicles of bla CTX-M-15 in E. coli and K. pneumoniae, as well as for other antibiotic genes conferring resistance to tetracyclines, aminoglycosides and fluoroquinolones present on IncFII plasmids along with ESBL genes [4,11,22]. Most of the K. pneumoniae isolates as well as other Enterobacteriaceae isolates, including multiresistant epidemiological clone E. coli B2-O25b-ST131, in this study harboured large IncFII K plasmids with multiple antibiotic resistance genes and showed conjugative ability to E. coli as well as Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms are surface-associated bacterial communities within which bacteria have up to 1,000 times higher resistance to antimicrobials and host defenses compared with their planktonic counterparts 2,3 . Biofilms present on the surface of medical devices provide the bacterial inocula for disease and can also serve as reservoirs of plasmids carrying antibioticresistance genes 4,5 . Most strategies for reducing biofilm-associated infections focus on the modification of existing materials that are used to manufacture in-dwelling medical devices by the incorporation of antibiotics 6,7 or other antimicrobials, such as silver salts, nitrofurazone, chlorhexidine, polymerized quaternary ammonium surfactants, antibacterial peptides and anionic nanoporous hydrogels [8][9][10][11][12][13][14][15] .…”
mentioning
confidence: 99%
“…23,25,26 Licht et al 27 showed that plasmid invasion was proficient in a biofilm during the initial contact phase, after which no further transfer was detected. In contrast, the efficiency of invasion was initially slower in mixed liquids but constant, and eventually allowed plasmid spread through the entire population.…”
Section: Spatial Structure: a Barrier For Horizontal Plasmid Spreadmentioning
confidence: 99%